Long-term (2001–2012) concentrations of fine particulate matter (PM2.5) and the impact on human health in Beijing, China - S. Zheng; A. Pozzer; C. X. Cao; J. Lelieveld (Atmospheric Chemistry and Physics, 2015)
Beijing, the capital of China, is a densely populated city with poor air quality. The impact of high pollutant concentrations, in particular of aerosol particles, on human health is of major concern. The present study uses aerosol optical depth (AOD) as proxy to estimate long-term PM2.5 and subsequently estimates the premature mortality due to PM2.5. We use the AOD from 2001 to 2012 from the Aerosol Robotic Network (AERONET) site in Beijing and the ground-based PM2.5 observations from the US embassy in Beijing from 2010 to 2011 to establish a relationship between PM2.5 and AOD. By including the atmospheric boundary layer height and relative humidity in the comparative analysis, the correlation (R2) increases from 0.28 to 0.62. We evaluate 12 years of PM2.5 data for the Beijing central area using an estimated linear relationship with AOD and calculate the yearly premature mortality by different diseases attributable to PM2.5. The estimated average total mortality due to PM2.5 is about 5100 individuals per year for the period 2001–2012 in the Beijing central area, and for the period 2010–2012 the per capita mortality for all ages due to PM2.5 is around 15 per 10 000 person-years, which underscores the urgent need for air pollution abatement.